Terminal efficiency of Peruvian university students in the second specialty programs of a dental school over seven years [version 2; peer review: 2 approved] - María Claudia Garcés-Elías; Cesar D. Rojas-Senador; Roberto A. León-Manco; Karla Lucero Avalos-Baltodano; Karen Llajaida Cabanillas-Yllesca (F1000Research)
Background Terminal efficiency (TE), the proportion of students completing academic programs within the expected timeframe, is a critical metric for assessing postgraduate health education quality, yet it remains underexplored in Latin American dental specialties. Efficient training is vital for producing competent professionals to meet regional healthcare demands. This study aimed to determine the TE of Peruvian university students in second specialty dental programs at a Peruvian university from 2017 to 2023. Methods A longitudinal, cross-sectional analysis was conducted using 257 complete records from the university institutional repository. Inclusion criteria encompassed full documentation of admission, academic status, and graduation dates. TE was calculated as the time from document submission to graduation, categorized as ≤1 year or ≥2 years. Statistical analyses included Chi-square tests, non-parametric Mann-Whitney U and Kruskal-Wallis tests, Poisson regression, and hierarchical multiple linear regression on log-transformed TE. Results: Mean TE was 0.93 years (SD=1.22), with 72.37% of students (n=186) completing within ≤1 year. Significant variations were observed by submission year (p=0.001) and specialty (p<0.001), with Oral and Maxillofacial Radiology (0.30 years) outperforming Periodontics and Implantology (1.76 years). The submission year was the only significant predictor of mean TE (β=0.144, p<0.001). Conclusion Dental programs of a Peruvian university demonstrate robust TE, though specialty-specific and temporal disparities highlight areas for improvement. Targeted interventions, such as streamlined thesis processes and specialty-specific support, could enhance efficiency, informing educational policy in Latin America.